(untitled) (International Journal of Biomedical Research, 2014)
Multiple myeloma is a clonal malignant neoplasm of plasma cells and is characterized by the secretion of monoclonal protein in plasma. Here, we report a case of biclonal multiple myeloma having two spikes on serum protein electrophoresis, one being in Beta-2 region and the other in gamma region. Further on immunofixation, both peaks were found to be of IgA-kappa variant. Biclonal gammopathy is a rare case, which accounts for only 1% of all myelomas but biclonal gammopathy of IgA kappa variant has not been described in the literature so far.